Специфические формы государственно-частного партнерства - Павлинчук, А.А. (Економічні інновації, 2012)
Мета статті полягає в тому, щоб визначити і описати специфічні форми державно-приватного партнерства (далі - ДПП), які найбільш ефективно працювали, і будуть працювати для створення стійкого розвитку й оптимального функціонування ринкової економіки держави. We have showed the experience of one farm, which has a positive experience in building sustainable financial results. We have developed a program of measures to achieve a positive financial result of agricultural manufacturer: the first - creation the material and technical base for own economic security, that is, expansion capacity for storage of crops; the second - to intensify its position on the exchange and secure the status of a powerful and independent producer. It is shown that these recommendations are not only for a particular research subject, but also for all farms.